Comparison of Hysterosalpingography and Combined Laparohysteroscopy for the Evaluation of Primary Infertility - Nigam, A.; Saxena, P.; Mishra, A. (Kathmandu University Medical Journal, 2017)
Background Hysterosalpingography (HSG) is a useful screening test for the evaluation of female infertility. Laparoscopy has proven role in routine infertility work up but role of hysteroscopy in an infertile patient with normal HSG for additional information is a subject of debate. Hysteroscopy permits direct visualization of the cervical canal and the uterine cavity and thereby helping in the evaluation of shape, and cavitary lesion. Objective To detect uterine abnormalities in infertile women by various approaches i.e. HSG and hysteroscopy and evaluating the role of combining hysteroscopy with laparoscopy for the evaluation of tubo-uterine factor for primary infertility. Method One twenty eight infertile women were evaluated and HSG was performed as a basic test for evaluation of tubes and uterine cavity. Women were subjected to combined laparoscopic and hysteroscopic examination on evidence of HSG abnormalities. In absence of any HSG abnormality, women were subjected to ovulation induction for three to six months and if they did not conceive during this period they were undertaken for combined laparo-hysteroscopic evaluation. Result The positive predictive value of HSG for detecting the intrauterine abnormalities was 70% among 126 patients where the hysteroscopy could be performed successfully. The diagnostic accuracy of HSG for intrauterine abnormalities revealed false negative rate of 12.96%. The most frequent pathologies encountered by laparoscopy were tubal and/or peritoneal and were found in 68% (87/128) of women. Total 64.06% infertile women had some abnormality on laparoscopy. This detection rate has been increased from 64.06% to 71.86% on including the concomitant hysteroscopy. Conclusion HSG is a good diagnostic modality to detect uterine as well as tubal abnormalities in infertile patient. HSG and hysteroscopy are complementary to each other and whenever the patient is undertaken for diagnostic laparoscopy for the infertility, hysteroscopy should be combined to improve the detection rate of abnormalities especially in communities where there is enormous risk of pelvic infection.